miR-124 acts During Drosophila Development to Determine the Phase of Adult Circadian Behavior. - Xia, Y.; Chen, C.; Emery, P. (Journal of Biological Rhythms, 2025)
The circadian clock enables organisms to optimize their metabolism, physiology, and behavior with the time-of-day. However, circadian rhythms benefit organisms only if they are properly synchronized with the day/night cycle; circadian misalignment can have detrimental effects on animals' wellbeing and survival. We previously showed that in Drosophila, loss of the microRNA miR-124 advances the phase of circadian evening locomotor activity by several hours under constant darkness conditions. Interestingly, we now report that loss of miR-124 also delays morning activity under a light/dark cycle with a short photoperiod. We recapitulated these opposite phase phenotypes by eliminating miR-124 during larval development, but not when this microRNA is lost during pupation to adulthood. The loss of miR-124 results in significant miswiring within the circadian neural network and severely alters neural activity rhythms in the ventral Lateral Neurons (s-LNvs) and the posterior Dorsal Neurons 1 (DN1ps), which control the timing of morning and evening activity. Silencing the s-LNvs in miR-124 mutant flies restores the phase of evening activity, while activating the DN1ps rescues the phases of both morning and evening activities. Our findings thus reveal the pivotal role of miR-124 in sculpting the Drosophila circadian neural network during development and its long-lasting impact on circuit activity and adult circadian behavior.